2009
DOI: 10.1002/bem.20540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal exposure to a 50‐Hz magnetic field on one‐trial passive avoidance learning in 1‐day‐old chicks

Abstract: We investigated memory impairment in newly hatched chicks following in ovo exposure to a 50-Hz magnetic field (MF) of 2 mT (60 min/day) on embryonic days 12-18. Isolated and paired chicks were used to test the effect of stress during training, and memory retention was tested at 10, 30, and 120 min, following exposure to a bitter-tasting bead (100% methylanthranilate). Results showed that memory was intact at 10 min in both isolated and paired chicks with or without MF exposure. However, while isolated chicks h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…There is increasing evidence that exposure to ELM can influence learning and memory, although some negative results have been reported [2], [3]. Previous studies have shown that ELM exposure impaired acquisition and consolidation of spatial memory in rodents [4][6] and produced deficits in detour learning and one-trial passive avoidance learning in chicks [7], [8]. Moreover, it has been reported that exposure to ELM impaired the performance of humans in word recognition and visual discrimination tasks [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that exposure to ELM can influence learning and memory, although some negative results have been reported [2], [3]. Previous studies have shown that ELM exposure impaired acquisition and consolidation of spatial memory in rodents [4][6] and produced deficits in detour learning and one-trial passive avoidance learning in chicks [7], [8]. Moreover, it has been reported that exposure to ELM impaired the performance of humans in word recognition and visual discrimination tasks [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, regarding the (i)reversibility of the induced effects, it would be interesting to establish the kinetics of the detected changes by measuring the population activity in a series of temporal points. Finally, the changes similar to the above-mentioned are involved in the regulation of some other neuronal processes in insects such as migration, orientation, learning and memory (Kafaee et al 2010, Sun et al 2010, Engels et al 2014), so our research may contribute to a better understanding of MF influence on animal and human physiology.…”
Section: Discussionmentioning
confidence: 89%
“…Intracellular Ca 2 homeostasis and oxidative reactions are essential for normal functioning of excitable cells (Aon et al 2008), thus the changes observed in our experiments may be a consequence of the increased production of free radicals after the exposure to MF. This is supported by the model of magnetoreception which is based on the existence of Cryptochrome photoreceptors (CRY) (Foley et al 2011), that generate magneticallysensitive radical pairs in chemical reactions (Ritz et al 2000, Todorović et al 2007) and others in the literature (Pozzi et al 2007, Liu et al 2008, Sun et al 2010, Ilijin et al 2011a, 2011b, Wang et al 2013, Ma et al 2014. M. funereus individuals do not expect intensified MF activity, so the change in the neuronal background activity was irreversible after the initial effect of sine wave MF-5.…”
Section: Discussionmentioning
confidence: 96%
“…Evaluation of behavioural neuroscience and cognitive tests CNS and auditory system are more influenced by 900 MHz EMF exposures. It was seen that after EMF exposure there is impairment of cognitive functions, addition to morphological and ultrastructural alterations using behavioural measurements such as reaction time and accuracy in cognitive test (Davis et al, 1984;Sun et al, 2010). Evidence of short-term memory loss after exposure to MWR is still controversial.…”
Section: Overview Of Synaptic Function By Electron Microscopic Applicmentioning
confidence: 98%